Assessment of ataxia phenotype in a new mouse model of galactose‐1 phosphate uridylyltransferase (GALT) deficiency. Issue 1 (25th October 2016) - Chen, Wyman; Caston, Rose; Balakrishnan, Bijina; Siddiqi, Anwer; Parmar, Kamalpreet; Tang, Manshu; Feng, Merry; Lai, Kent
Abstract: Despite adequate dietary management, patients with classic galactosemia continue to have increased risks of cognitive deficits, speech dyspraxia, primary ovarian insufficiency, and abnormal motor development. A recent evaluation of a new galactose‐1 phosphate uridylyltransferase (GALT)‐deficient mouse model revealed reduced fertility and growth restriction. These phenotypes resemble those seen in human patients. In this study, we further assess the fidelity of this new mouse model by examining the animals for the manifestation of a common neurological sequela in human patients: cerebellar ataxia. The balance, grip strength, and motor coordination of GALT‐deficient and wild‐type mice were tested using a modified rotarod. The results were compared to composite phenotype scoring tests, typically used to evaluate neurological and motor impairment. The data demonstrated abnormalities with varying severity in the GALT‐deficient mice. Mice of different ages were used to reveal the progressive nature of motor impairment. The varying severity and age‐dependent impairments seen in the animal model agree with reports on human patients. Finally, measurements of the cerebellar granular and molecular layers suggested that mutant mice experience cerebellar hypoplasia, which could have resulted from the down‐regulation of the PI3K/Akt signaling pathway.